CD40 signalling induces IL-10-producing, tolerogenic dendritic cells - Tüttenberg, Andrea; Fondel, Sabine; Steinbrink, Kerstin; Enk, Alexander; Jonuleit, Helmut (Experimental dermatology, 2010)
Abstract: Dendritic cells (DC) are potent antigen-presenting cells capable to induce efficient antigen-specific T cell responses in vitro and in vivo. Herein, the maturation process is of great significance, as immature DC (iDC) are known to induce rather regulatory than effector T cell differentiation. This study was designed to characterize the role of the CD40-CD40L pathway for differentiation and function of human DC. Therefore, iDC were stimulated through CD40-CD40L interaction by transduction of DC with adenoviral vectors encoding for CD40L (Ad-CD40L). Resulting DC (CD40L-DC) were analysed concerning their phenotype, cytokine profile and T cell stimulatory capacity. Transduction induced a DC phenotype comparable to stimulation with proinflammatory cytokines as revealed by upregulation of CD83 and the costimulatory molecules CD80 and CD86. Additionally, Ad-CD40L-induced strong production of IL-12p70 not observed in cytokine-matured DC. Surprisingly, the T cell stimulatory capacity was markedly reduced in CD40L-DC. Furthermore, stimulation of CD8+ T cells by peptide-loaded CD40L-DC resulted in a substantial reduction of antigen-specific IFN-γ production. This phenomenon is due to an enhanced IL-10 production of CD40L-DC in DC-T cell coculture as well as a stabilization of the IL-10 receptor expression on activated T cells. These data demonstrate that DC stimulated through CD40-CD40L interaction differentiate into tolerogenic DC with immunomodulatory function.
Erstmals am 15 December 2009 online veröffentlicht
Gesehen am 19.01.2024